PENGARUH PENEMPATAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA CV. SKS BIMA - Fauzi, Muhammad; Kusumayadi, Firmansyah (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This study aims to determine the partial significant effect of work placement on employee performance at CV. SKS Bima, work stress partially significant effect on employee performance at CV. SKS Bima, work placement and work stress have a simultaneous effect on employee performance at CV. SKS Bima. . The instrument in this study used a questionnaire with a Likert scale measurement. The population in the study of all employees at CV.SKS Bima as many as 80 employees consisting of 1 Manager, 2 Supervisors, 16 Admins, 20 Delivery people, 12 Warehouse Sections, 29 Sales people. The sample in this study were employees as respondents amounted to 80 people using saturated sampling. Data collection techniques using observation, interviews, questionnaires, literature study. The data analysis technique used validity test, reliability test, classical assumption test, multiple linear regression, correlation coefficient, coefficient of determination, t test, and f test. The results of the study indicate that work placement has a partial effect on employee performance at CV. SKS Bima, Job stress has no effect on employee performance at CV. SKS Bima, work placement and work stress have a simultaneous effect on employee performance at CV. SKS Bima.